Telemonitoring for hypertensive disease in pregnancy. (3rd August 2019) - Khalil, Asma; Perry, Helen; Lanssens, Dorien; Gyselaers, Wilfried
ABSTRACT: Introduction : Telemonitoring of hypertension in pregnancy is becoming increasingly common. Several small studies have described the potential benefits of patient-led remote monitoring, including fewer hospital visits, better blood pressure control, and cost savings. Areas covered : This review summarises the principles of prenatal remote monitoring of hypertension as well as the types of devices and applications currently in use. We summarise current evidence regarding the potential benefits and pitfalls with respect to outcomes for mothers, neonates and wider population health. Core topics for ongoing and future research are discussed, with special emphasis on feasibility and validation of technologies, methodological standardization, patient safety, privacy and acceptability, and health economics and governance. Expert opinion : Telemonitoring of hypertension in pregnancy is likely to become commonplace in the next five to ten years and research now must be directed to ensure it is used in the safest way before its general introduction into daily clinical practice can be recommended. Raising women's awareness of their health condition could improve both pregnancy and long-term health outcomes.